CELLULASE PRODUCTION BY Bacillus subtilis M1 USING PRETREATED GROUNDNUT SHELL–BASED LIQUID STATE FERMENTATION - Ashish Kr Vyas; Chayanika Putatunda; Joginder Singh; Deepak Vyas (SEAMEO BIOTROP, 2016)
Groundnut shell, which is rich in natural cellulose, was assessed as a substrate for the production of cellulase enzyme by cellulolytic bacteria. In the present investigation, the bacterial isolate M1 was found to be capable of producing high amounts of endoglucanase and exoglucanase on alkali-treated groundnut shell. The effects of various nitrogen sources, amino acids, and Ca²⁺ ions in the medium containing pretreated groundnut shell were also evaluated. It was observed that a 2% substrate concentration and 1 mM calcium concentration were optimal for cellulase production. Among the nitrogen sources tested, ammonium nitrate was found to be the most effective. Asparagine, tryptophan, and methionine were found to stimulate cellulase activity.